Endowment redistribution and Pareto improvements in GEI economies - Concetta Mendolicchio; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
With incomplete markets and numeraire assets, there are open sets of economies such that their equilibrium allocations can be improved upon by a reallocation of period zero endowments. This strengthens the classical results on constrained Pareto ineffciency of equilibria in GEI. – – Bei unvollkommenen Märkten und numerairen Vermögen gibt es eine offene Menge an Volkswirtschaften, so dass die Gleichgewichtsverteilung durch eine veränderte Anfangsverteilung verbessert werden kann. Dies stärkt das klassische Ergebnis der eingeschränkten Pareto Ineffizienz von Gleichgewichten in GEI.
Keywords: D51; D52; 330; GEI; constrained Pareto optimality